Socialization and Education of Regulations Regarding Customs for Small Entrepreneurs During the Covid-19 Pandemic in Batam City - Puspitasari, Ayu; Hati, Shinta Wahyu; Mulyaningtyas, Dian; Harlan, Fandy Bestario; Kartikasari, Dwi; Ersya, Ozy Diva; Zuliarni, Sri; Septiana, Maryani; Wibowo, Seto Sulaksono Adi; Zelmiyanti, Riri; Sahendra, Rezihardi; Hasanah, Raja Fillandini Nurul; Annisa, Nur; Kastella, Cantika Yosdianti; S.M., Ilham (Politeknik Negeri Batam, 2023)
Socialization and education regarding customs regulations for small entrepreneurs will be very useful for the development of Small Businesses, which is very important in the current conditions, where the Covid-19 pandemic has an impact on the national economy, especially for Batam. This service leads to socialization and education of regulations related to customs for small entrepreneurs. This community service activity aims to provide socialization and education related to customs regulations for micro, small and medium enterprises in the midst of the COVID-19 pandemic. The target of this service is SMEs in Batam. The purpose of this service is to: 1. Provide socialization of customs regulations for small entrepreneurs in Batam. 2. Provide education on customs regulations for small entrepreneurs in Batam. 3. Know the understanding of small entrepreneurs about customs regulations that encourage exports for small entrepreneurs and understand the understanding of shipping regulations. The method that will be implemented is by conducting online training, providing pocket books and motion graphics videos. The expected result is the existence of pocket books and motion graphics videos that can be accessed by small business actors, MSMEs, companies and the community. This service is one of the implementations of Project-Based Learning for courses in international trade law and taxation as well as international trade.